2011
DOI: 10.1007/s00775-011-0796-5
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic vanadium compound and membrane interfaces: interface-facilitated metal complex hydrolysis

Abstract: The interactions of metabolites of the antidiabetic vanadium-containing drug bis(maltolato)oxovanadium(IV) (BMOV) with lipid interface model systems were investigated and the results were used to describe a potentially novel mechanism by which these compounds initiate membrane-receptor-mediated signal transduction. Specifically, spectroscopic studies probed the BMOV oxidation and hydrolysis product interaction with interfaces created from cetyltrimethylammonium bromide (CTAB) which mimics the positively charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 69 publications
2
70
0
Order By: Relevance
“…Many studies have been carried out in vivo and ex vivo to understand how these compounds act to develop new and superior compounds. [7][8][9]13,22,25,26,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] The modes of action of vanadium compounds are poorly understood, in part because the compounds exert insulin-like effects, which are very involved. In addition, these coordination compounds undergo hydrolytic and redox reactions as well as protonation and oligomerization reactions.…”
Section: Biological Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been carried out in vivo and ex vivo to understand how these compounds act to develop new and superior compounds. [7][8][9]13,22,25,26,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] The modes of action of vanadium compounds are poorly understood, in part because the compounds exert insulin-like effects, which are very involved. In addition, these coordination compounds undergo hydrolytic and redox reactions as well as protonation and oligomerization reactions.…”
Section: Biological Implicationsmentioning
confidence: 99%
“…[7][8][9][10] V 10 forms from vanadium in oxidation state +5 and is particularly stable at acidic pH. Recently, studies of how vanadium compounds interact with interface model systems and traverse membranes [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] have shown that several anionic complexes readily penetrate the interfaces, [16,17,20,21,26] but large oxometalates such as V 10 reside away from a negatively charged interface and close to a positively charged interface, as expected. [19][20][21]23,24,27,28] Because counterions can affect the properties, a suitable counterion choice could poten-By using 51 V NMR spectroscopy, we found only small differences between the metformium and Na + decavanadate materials.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, positively charged surfactants are considered to be a good model for the PC head group and are used as lipid substitutes. 40 Micelles that are formed by mixtures of lipids and detergents are called mixed micelles. It should be pointed out that the CMC as well as the average number of detergent molecules per micelle can be signifi cantly changed when lipids or proteins are added to the micelles.…”
Section: Vesicular Model Membranesmentioning
confidence: 99%
“…Using NMR spectroscopy, Crans and coworkers investigated the interactions of the antidiabetic vanadium-containing drug bis(maltolato)oxovanadium (IV) (BMOV) with a lipid interface in a CTAB micelle system and concluded that the drug penetrated the lipid interface, becoming located near the charged head groups. 40 The nature and strength of the interactions between a cationic fl uorophore, rhodamine 123 (R123), and surfactants of different head charge were investigated by Freire and coworkers. 46 Their results showed the complex physicochemical and photophysical behaviour of a charged dye in micellar systems, which resembles the situation expected in biological membranes.…”
Section: Vesicular Model Membranesmentioning
confidence: 99%
“…[6] The element is present in vanadium-containing enzymes such as nitrogenase and haloperoxidases. [7] Due to structural similarity between vanadates and phosphate and being able to be transported into cells through the anion channel of the plasma membranes, [8,9] many vanadium compounds have been shown to increase glucose transport into cells and its oxidation via glycolysis. [10,11] Oxovanadium (IV) sulphate has demonstrated to possess oral insulin-like activity similar to that of the vanadates, with lowered toxicity.…”
Section: Introductionmentioning
confidence: 99%